Audit committees in oil companies and their role in improving internal control systems: A case study of the National Well Services Company (ENTP) - djazouli, abdelfettah; latreche, walid (Journal of Research in Finance and Accounting, 2025)
This study aims to explore the role of audit committees in assessing the effectiveness of internal control systems, with a particular focus on the National Company for Works in Wells (ENTP). To gather empirical evidence, interviews were conducted with company officials, and a total of 45 questionnaires were distributed within the organization. Of these, 39 valid responses were collected, transcribed, and analyzed using the Statistical Package for the Social Sciences (SPSS). The findings indicate a significant and positive relationship between the audit committee's activities and the performance of the internal control system. Specifically, the audit committee contributes to strengthening internal controls by overseeing the internal audit function, coordinating with the external auditor, and ensuring the quality and reliability of financial reporting. These efforts collectively enhance the overall governance framework within petroleum companies operating in Algeria